'A Fund of entertaining and useful Information': Coffee Houses, Early Public Libraries, and the Print Trade in Eighteenth-Century Dublin. (February 2014) - Abbas, Hyder
Abstract In eighteenth-century Dublin, coffee houses were early public information centres while circulating and subscription libraries acted as early public libraries. These institutions offered services — facilitated by their close relationship with the print trade — that preceded today's public library provision. This paper examines the functions and procedures of Dublin's early public libraries and their interconnectivity with the print trade. While Marsh's Library stands out as a public library during this time, other institutions provided a rudimentary public library service in the eighteenth century.